Toxic Friendship and Mental Health Among University Students: An Integrative Psychological and Qur’anic Analysis - Hanipah; Muhammad Daffa Syafiq Nashr Ad-Diba’i (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Toxic friendship in university settings has increasingly emerged as a destructive form of peer relationship characterized by manipulation, excessive control, jealousy, and a lack of empathy, posing a significant threat to students’ mental health and social well-being. This study aims to examine the impact of toxic friendship on students’ mental health and to formulate an ethical-preventive framework based on Dr. Lilian Glass’s psychological theory and the interpretive perspective of Tafsir Al-Misbah. This research employs a qualitative approach using a critical integrative literature review method, incorporating thematic analysis of relevant primary and secondary sources, including Toxic People, the Qur’an, Tafsir Al-Misbah, and recent scholarly publications. The findings indicate that toxic friendship contributes to decreased self-esteem, heightened levels of stress, anxiety, and depression, as well as overthinking, social isolation, and diminished academic performance. Furthermore, M. Quraish Shihab’s interpretation of QS. Al-Furqan (25:28) and QS. Al-Hujurat (49:10-12) in Tafsir Al-Misbah underscores the importance of cultivating healthy relationships, maintaining ethical speech, and avoiding suspicion, gossip, and relational harm. Toxic friendship adversely affects students’ psychological well-being and social relationships, while Tafsir Al-Misbah offers a normative ethical foundation for fostering healthy, supportive, and value-based social bonds (ukhuwah).